Application of finite element analysis on balloon expandable coronary stents: A review - Bekal, Chandrakantha; Hiroshi Yamada, Dr.; Ranjan Shetty, Dr.; Satish Shenoy, Dr. (International Journal of Engineering and Technology, 2018)
Numerical analysis of complex physical environment continues to be preferred over â€œbuild and testâ€ approach in product development process. Finite Element Analysis (FEA) of coronary artery stenting is studied and researched worldwide for many years. Potential of using FEA for mimicking in-vivo is high as experimental test is ruled out for variety of reasons. This review aims at discussing issues and challenges of numerical simulation based on part of available literature on usage of FEA techniques for investigating behavior of balloon expandable (BE) coronary stents inside artery. Literatures of past 16 years of study on the structural analysis is summarized and potential issues for research is discussed. Study tries to investigate deployment characteristics and biomechanical response of artery post stenting and significance of non-physiological conditions induced. Effects of geometrical parameters, simulation strategies are summarized. Study mainly underscores the potential challenges of reliable numerical investigation. Scope of FEA in predicting contributor for in-stent restenosis (ISR), a major drawback of stenting procedure, by correlating the engineering aspect of stent design and its clinical significance supported by clinical trials are highlighted. Study is expected to serve as qualitative assessment for cardiologists to minimize procedural failure and quantitative tool for the designers for stent optimization.Â Â